Social media addiction and personality dimensions among Tunisian medical students - Guermazi, Fatma; Abid, Wissal; Baati, Imen; Cherif, Farah; Mziou, Emna; Mnif, Dorra; Feki, Ines; Masmoudi, Rim; Masmoudi, Jawaher (Frontiers in Psychiatry, 2024)
Purpose: Social media (SM) has become a common activity for today's young people. It is sometimes overused and potentially results in SM addiction. This study aims to assess SM addiction and its associated factors in medical students and to examine its relationship with dimensions of personality global self-esteem, and social self-esteem.We carried out a cross-sectional study among a sample of medical students in the region of Sfax in Tunisia. Social Media Addiction Scale-Student Form (SMAS-SF), Big Five Inventory, Rosenberg Self-Esteem Scale, and Social Self-Esteem Inventory were used to collect data.Results: Overall, 116 medical students were included in the survey. The median age of the participants was 26 years, and 91 students (78.4%) were female. Almost half of them (55.20%) were enrolled in the third cycle. The most widely used SM was Facebook (98.3%). Students with the highest SMAS-SF scores had a significantly younger age of first use (p=0.011, r=-0.235), spent more time on their favorite SM (p=0.005, r=0.260), and performed more activities on SM, namely: making comments (p=0.005), browsing SM profiles (p=0.018), and posting videos (p=0.007) or pictures (p=0.002). The need to establish an identity was significantly associated with higher SMAS-SF scores (p=0.011). We also found that neuroticism and a low level of conscientiousness were linked to high SMAS-SF scores (p=0.006, r=0.252 and p=0.050, r=-0.183, respectively). Moreover, high SMAS-SF scores were significantly related to lower global and social self-esteem scores (p=0. 015, r=-0.226 and p=0.032, r=-0.199, respectively).Our results highlight the critical need to take into consideration the evaluation and intervention of self-esteem and personality dimensional issues to target interventions for SM addiction among medical students.